Análisis del sistema actual de riego y productividad para la implementación de un sistema automático de riego controlando los parámetros de temperatura y humedad mediante sistema HMI en la finca “San Nicolas” sector de Illuchi ubicado en el barrio juan pablo segundo en el cantón Latacunga, provincia de Cotopaxi en el periodo 2015-2016 - Pruna Campaña, Cristian Marcelo (2016)
This work is intended to provide a method of easy application and better use of water resources in irrigation work for increased production of grass. This project promotes proper water management based on automatic processes that censused levels of soil moisture through a sprinkler irrigation development, based technology in the automation and control valves for the system. This work consists of equipment selection and implementation of a sprinkler system, which provides a suitable sheet of water to maintain adequate pasture production. The automatic mentioned works by grouping hydraulic, electrical and control systems that provide irrigation to pasture elements. The hydraulic part is the transport of water from the mains to the reservoir tank and then to the sprinklers, this part consists of: main and secondary pipelines working according to water pressures in the sector….